PENENTUAN FEE AUDIT TERHADAP INDEPEDENSI AUDITOR - Rohmaniyah, Rohmaniyah (Fakultas Ekonomi, Program Studi Akuntansi, 2017)
Fee is a fee received by a public accountant after carrying out its audit services, the amount depends on the assignment risk, the complexity of the services provided, the level of expertise required to execute the service, the corresponding KAP cost structure. Indepedence is a mental attitude that is free from influence, not controlled by other parties. This research uses descriptive qualitative approach. Sources of data in this study in the form of primary data. Data obtained through interviews with auditors recorded by unstructured / non-formal. Informants in this study is one of the auditors who work in KAP Lisa Buntaran who have sufficient experience in auditing. The results of this study indicate that in practice the audit fee is determined by the KAP and there is bargaining with the client. Additional fees will exist when the client requests to investigate the findings listed on the paper to be further explored. The auditor's indepedence is not affected by fees paid by the client. KAP still uphold the independence and keep following the professional code of ethics. The effectiveness of auditor audits looks at prepared papers and analyzes paperwork originating from clients and third parties.